Larval study revealed diversity and life‐history traits of crypto‐benthic eel gobies - Maeda, Ken; Hanahara, Nozomi; Uehara, Masato; Tachihara, Katsunori (Journal of fish biology, 2022)
Because adult and juvenile eel gobies usually hide within the burrows of muddy substrates, their diversity and life history have not yet been fully elucidated. We investigated larval specimens of the eel gobies collected on Okinawa Island in southern Japan. The genus Trypauchenopsis was previously thought to consist of only one species, but our larval collection identified two species, Trypauchenopsis limicola and Trypauchenopsis intermedia, distinguished by their species‐specific melanophore arrangements and differences in their fin‐ray counts. Taenioides kentalleni were previously known from only two specimens worldwide. A third specimen of this species has now been added from the larval collection. In addition to the three species above, Taenioides gracilis and Caragobius urolepis were identified and the larval morphologies of the five species were described for the first time. All the larvae collected in the present study were at late postflexion stage. T. limicola, T. intermedia and T. gracilis were presumably collected in the estuaries and beaches when approaching their adult habitats at the end of pelagic life. They were 8.5–10.3 mm in standard length, and otolith analysis suggests that their pelagic larval durations are a little longer than 1 month (average 34–37 days). The larval occurrence suggested that the spawning season of T. limicola is May–December, when the water temperature is warmer than approximately 20°C. Our work reveals that studying the larval stage can provide new information on the taxonomy and life history of the elusive cryptobenthic fish.